Hot spots policing and crime reduction: an update of an ongoing systematic review and meta-analysis - Braga, Anthony Allan (Journal of experimental criminology, 2019)
This updated systematic review assesses the effects of focused police crime prevention interventions at crime hot spots. The review also examined whether focused police actions at specific locations result in crime displacement or diffusion of crime control benefits.